PENGARUH MODEL CIRC BERBANTUAN FLIPBOOK DIGITAL TERHADAP KEMAMPUAN MEMBACA KRITIS PESERTA DIDIK - Syaila Nur Fatimah; Arifin Ahmad; Feby Inggriyani (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study was motivated by the low critical reading skills of students at SDN 037 Sabang and the limited innovation in the learning process. The research aimed to examine the effect of the Cooperative Integrated Reading and Composition (CIRC) model assisted by digital flipbook media on students’ critical reading skills. A quantitative approach with a quasi-experimental method and nonequivalent control group design was applied. The sample consisted of 54 fourth-grade students selected through purposive sampling, with class IV C as the experimental group and class IV D as the control group. The learning process was carried out smoothly and effectively. During the planning stage, the researcher prepared instructional modules and critical reading assessment instruments. Throughout the learning activities, the classroom environment remained conducive, and students actively participated and responded well to the material. After implementing the CIRC model with digital flipbook assistance, the experimental class demonstrated improved critical reading skills. The average score increased from 50.33 (pretest) to 86.48 (posttest), while the control class improved from 48.41 to 76.89. The t-test showed a significance value of 0.046 (< 0.05), indicating a significant difference between the two classes. The experimental class also achieved an N-Gain score of 79.60 (high category) and an effect size of 1.90 (large category). These findings suggest that the CIRC model, when supported by digital flipbook media, has a significant and positive impact on enhancing students’ critical reading abilities, making it an effective strategy to foster deeper reading comprehension and analytical thinking in elementary education.